Emerging Role of Lipids in Metabolism and Disease (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Even though initially considered as a passive means for storing energy, lipids are now regarded as multifaceted molecules with crucial structural and functional activities. For instance, some of them play essential roles as key components of cell membranes whereas others act as signaling molecules in the regulation of cell homeostasis. In recent years, lipid research has attracted increasing interest because of the involvement of this class of compounds in human health. Indeed, a plethora of pathological conditions are characterized by alterations in lipid metabolism, such as cardiovascular diseases and brain disorders. This Special Issue is a collection of papers from different experts in lipid research, with the aim of providing new insights into the physiopathological involvement of lipids and their impact on human health. This collection also demonstrates the usefulness of interdisciplinary approaches in the development of novel methods to study and manipulate lipid metabolism, which may represent an attractive target for designing effective therapeutic strategies to counteract numerous pathologies.